Factors Affecting Firm’s Annual Turnover in Selected Manufacturing Industries of India: An Empirical Study - Singh , Ajay K.; Jyoti, Bhim (Business Perspective Review, 2020)
Purpose: This study makes a comparison of the manufacturing sector and its determinants for India and selected Asian countries. It examines the factors affecting the annual turnover of randomly selected 154 firms in seven different industries of the Indian manufacturing sector. Methods: In this study, the firm’s annual turnover is used as a dependent variable. Labor productivity, age, investment on plant & machinery, annual expenditure on marketing, total employees, production technology up-gradation, shortage of skilled workers, skills to improve the process, use of hi-tech tool and technique in production activities, technology transfer abilities, in-house R&D expertise, quality certification, foreign collaboration, waste management capabilities and building capacity of firms are used as independent variables. Regression coefficients of explanatory variables are assessed using linear, log-linear, and non-linear regression models. Results: The study concluded that the firm’s annual turnover has a significant association with technological development related variables, labor productivity, age, technology transfer abilities, in-house R&D expertise, quality certification, and waste management practices of firms. Implications: It suggests that Indian policymakers need to adopt a strong IPRs, education, and S&T policy in research institutions. India needs to increase R&D expenditure and researchers in research institutions. Research institutions should collaborate with the existing industries to discover more technologies and innovations for the manufacturing sector. All research organizations must set up technology transfer offices to increase technology transfer and commercialization. Furthermore, India needs to set up hi-tech firms to face global challenges. Originality: It uses primary data of 154 firms which are collected from seven different industries across Indian states. Thus, the study substantially contributes to the existing literature. Limitations: This study considers seven different industries that have high diversity in socio-economic, science & technological and IPRs related activities, technology transfer, commercialization of technology, and association with research institutions. Therefore, this study cannot provide policy suggestions for a specific industry.